Building democracy in South Asia : India, Nepal, Pakistan - Chadda, Maya. (Boulder : Lynne Rienner Publishers, 2000)
This analysis of South Asia's political experience with democracy in the 1990s assumes that, if democratic norms are to be universalized, they must first absorb the interpretations and experiences of the non-Western countries.
Includes bibliographical references and index.
Keywords: Democracy -- India; Democracy -- Nepal; Democracy -- Pakistan; Democratization -- India; Democratization -- Nepal; Democratization -- Pakistan